CK2 activity is required for the interaction of FGF14 with voltage‐gated sodium channels and neuronal excitability. Issue 6 (25th February 2016) - Hsu, Wei‐Chun J.; Scala, Federico; Nenov, Miroslav N.; Wildburger, Norelle C.; Elferink, Hannah; Singh, Aditya K.; Chesson, Charles B.; Buzhdygan, Tetyana; Sohail, Maveen; Shavkunov, Alexander S.; Panova, Neli I.; Nilsson, Carol L.; et al.
ABSTRACT: Recent data shows that fibroblast growth factor 14 (FGF14) binds to and controls the function of the voltage‐gated sodium (Nav) channel with phenotypic outcomes on neuronal excitability. Mutations in the FGF14 gene in humans have been associated with brain disorders that are partially recapitulated in Fgf14 –/– mice. Thus, signaling pathways that modulate the FGF14:Nav channel interaction may be important therapeutic targets. Bioluminescence‐based screening of small molecule modulators of the FGF14:Nav1.6 complex identified 4, 5, 6, 7‐tetrabromobenzotriazole (TBB), a potent casein kinase 2 (CK2) inhibitor, as a strong suppressor of FGF14:Nav1.6 interaction. Inhibition of CK2 through TBB reduces the interaction of FGF14 with Nav1.6 and Nav1.2 channels. Mass spectrometry confirmed direct phosphorylation of FGF14 by CK2 at S228 and S230, and mutation to alanine at these sites modified FGF14 modulation of Nav1.6‐mediated currents. In 1 d in vitro hippocampal neurons, TBB induced a reduction in FGF14 expression, a decrease in transient Na + current amplitude, and a hyperpolarizing shift in the voltage dependence of Nav channel steady‐state inactivation. In mature neurons, TBB reduces the axodendritic polarity of FGF14. In cornu ammonis area 1 hippocampal slices from wild‐type mice, TBB impairs neuronal excitability by increasing action potential threshold and lowering firing frequency. Importantly, these changes in excitability are recapitulated in Fgf14 –/– mice, and deletion of Fgf14 occludes TBB‐dependent phenotypes observed in wild‐type mice. These results suggest that a CK2‐FGF14 axis may regulate Nav channels and neuronal excitability.—Hsu, W.‐C. J., Scala, F., Nenov, M. N., Wildburger, N. C., Elferink, H., Singh, A. K., Chesson, C. B., Buzhdygan, T., Sohail, M., Shavkunov, A. S., Panova, N. I., Nilsson, C. L., Rudra, J. S., Lichti, C. F., Laezza, F. CK2 activity is required for the interaction of FGF14 with voltage‐gated sodium channels and neuronal excitability. FASEB J. 30, 2171–2186 (2016). www.fasebj.org